The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/jcm9092836
|View full text |Cite
|
Sign up to set email alerts
|

Folate Insufficiency Due to MTHFR Deficiency Is Bypassed by 5-Methyltetrahydrofolate

Abstract: Adequate levels of folates are essential for homeostasis of the organism, prevention of congenital malformations, and the salvage of predisposed disease states. They depend on genetic predisposition, and therefore, a pharmacogenetic approach to individualized supplementation or therapeutic intervention is necessary for an optimal outcome. The role of folates in vital cell processes was investigated by translational pharmacogenetics employing lymphoblastoid cell lines (LCLs). Depriving cells of folates led to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…It appears that unfavorable MTHFR(677) genotypes require additional factors to overcome the metabolic defects caused by low MTHFR activity, otherwise the genetic factor by itself would impair fetal growth. An experimental study showed that folate supplementation in a cell line with low MTHFR activity did not significantly increase the concentration of 5-MTHF, the biologically active folate, when compared with normal MTHFR activity cells [ 43 ]. Thus, the metabolic defects caused by genetic polymorphisms of the gene encoding the MTHFR enzyme may require supplemental 5-MTHF to overcome such defects [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that unfavorable MTHFR(677) genotypes require additional factors to overcome the metabolic defects caused by low MTHFR activity, otherwise the genetic factor by itself would impair fetal growth. An experimental study showed that folate supplementation in a cell line with low MTHFR activity did not significantly increase the concentration of 5-MTHF, the biologically active folate, when compared with normal MTHFR activity cells [ 43 ]. Thus, the metabolic defects caused by genetic polymorphisms of the gene encoding the MTHFR enzyme may require supplemental 5-MTHF to overcome such defects [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study showed that folate supplementation in a cell line with low MTHFR activity did not significantly increase the concentration of 5-MTHF, the biologically active folate, when compared with normal MTHFR activity cells [ 43 ]. Thus, the metabolic defects caused by genetic polymorphisms of the gene encoding the MTHFR enzyme may require supplemental 5-MTHF to overcome such defects [ 43 ]. Moreover, previous studies have demonstrated the excellent safety profile for the Calcium L-5-methyltetrahydrofolic acid (L-5-MTHF-Ca).…”
Section: Discussionmentioning
confidence: 99%
“…The L. casei microbiological assay was used in this study. However, methods of folate detection, such as LC–MS/MS, could produce more accurate and specific measurements of folate and its metabolites in serum and tissues, while being less susceptible to interference from antibiotics and contaminants [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…FA, FLA and 5MTHF share the same transporter and receptor. In vitro experiments have shown that cells with low MTHFR activity require 5-MTHF [ 19 ]; 5-MTHF cannot bypass mutations at the levels of methionine synthase or the receptors/transporters.…”
Section: L Methylfolate (5-mthf)mentioning
confidence: 99%
“…Unmetabolized FA in plasma occurs regularly following FA supplementation, but rarely with 5-MTHF [ 31 ]. High doses of folic acid can induce a pseudo MTHFR syndrome simply via a Michaelis and Menten effect on enzymes that have a weak/slow activity [ 18 , 19 , 40 ]. Determining the real impact of UMFA in infants is important: it is a common feature in countries that implement an FA fortification program.…”
Section: Folate Malabsorptionmentioning
confidence: 99%